Systematic comparison of exosomal proteomes from human saliva and serum for the detection of lung cancer - Sun, Yan; Liu, Sha; Qiao, Zhi; Shang, Zhi; Xia, Zhijun; Niu, Xiaomin; Qian, Liqiang; Zhang, Yan; Fan, Liuyin; Cao, Cheng-Xi; Xiao, Hua (Analytica chimica acta, 2017)
Circulating tumor exosomes harbor plenty of cancer biological information, which have emerged as promising targets for cancer early detection and diagnosis. Human serum and saliva are unique diagnostic body fluids, which contain numerous circulating exosomes. It is necessary to establish standardized isolation method and compare their proteome profiling for translational medicine. High abundant proteins in these body fluids were removed before exosomes isolation and obtained exosomes were further confirmed by morphology analysis and surface biomarker test. Label free quantification was applied to systematically compare the protein profiling in saliva and serum exosomes. 319 and 994 exosomal proteins were identified from saliva and serum by LC-MS/MS, respectively. To explore their utility for cancer proteomics, we systematically compared the proteome of saliva and serum exosomes from healthy subjects and lung cancer patients. In particular, 11 potential candidates were coincidently discovered in both body fluids of lung cancer patients. Our finding enforced the hypothesis that cancer related proteins were presented in saliva and serum exosomes, which promoted the unique features of exosomes in our body fluids. A circulating exosomes based body fluid test could be easily established for monitoring cancer once these candidates were validated. [Display omitted] •319 and 994 exosomal proteins were identified from human saliva and serum, respectively.•Around 80% of salivary exosomal proteins were shared with serum exosomes.•11 exosomal proteins were coincidently discovered in saliva and serum for the detection of lung cancer.